Enhancing critical thinking through differentiated challenge-based STEM context learning integrated AI-Website: An analysis of adversity quotient - Wahid Jauhari; Adi Satrio Ardiansyah; Eny Agustianingsih (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2026)
Society 5.0 transforms education, urging students to develop their critical thinking for complex problems. Indonesia's low proportion of students with these skills highlights the need to develop learning innovations. Beyond innovations, this research also considers affective factors like the Adversity Quotient in their impact on critical thinking. On the other hand, there has been no research that integrates Challenge-Based STEM Context Learning, AI-Websites, and differentiated learning simultaneously and examines the influence of AQ within that framework. Therefore, this study aims to determine the effectiveness of differentiated CBL-STEM Context learning integrated by AI-Website to improve critical thinking skills, analyze the influence of AQ on critical thinking skills, and describe those critical thinking skills based on the students' AQ categories. This research used a mixed-method with a sequential explanatory design in all eighth-grade students at one of the state junior high schools in Semarang, represented by two sample groups. Conducted over four weeks, it collected quantitative data through tests and questionnaires, and qualitative data via interviews. Quantitative data were analysed with R software, while qualitative data were condensed and compared to assess critical thinking skills indicators. The results show that the learning model effectively improved students’ critical thinking skills, with the experimental group achieving a 75.6% improvement. Regression analysis indicated that the adversity quotient contributed only 8.4% to critical thinking skills in this learning. Field interviews show students meet interpretation and analysis indicators across AQ categories, with differences in other critical thinking areas. This study suggests that similar research should include AQ differentiation in the learning process.